Implementation of entrepreneurship education in increasing student entrepreneurship skills - Denti Anggiran, Nafisha; Zamhari, Ahmad; Aprilia, Tiara; Firliana, Dini; Ambar, Ambar (ARKA INSTITUTE, 2023)
Entrepreneurship education is interpreted as a science that is studied by students in higher education institutions that involve students to develop their skills and potential by thinking creatively, being innovative and taking risks. In order to fulfill the desire for entrepreneurship, skills are needed for students so that they can optimal in entrepreneurship. How is the application of entrepreneurship education in improving student entrepreneurship skills. This study aims to determine the application of entrepreneurship education in improving student entrepreneurship information. The research method used is descriptive qualitative with data collection techniques using questionnaires or questionnaires to respondents via the Google form to 20 students. The results of this study indicate that 86.88 percent of students have the same perception that the application of entrepreneurship education can improve student entrepreneurship skills. It can be concluded that the application of entrepreneurship education can improve student entrepreneurship skills.